Survey of leaf-cutting ant species in native vegetation and monocultures in the State of Goiás, Brazil - Arruda, Filipe Viegas de; Pesquero, Marcos Antônio; Pesquero, Marcos Filipe; Santos, João Danilo dos (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
Leaf-cutting ants are distributed exclusively in the Americas. For this study, we sampled different areas of native vegetation and monocultures to survey the leaf-cutting ants that occur in the State of Goiás, and to what environments they are associated. We recorded six species of leaf-cutting ants: Atta sexdens, Atta laevigata, Acromyrmex subterraneus, Acromyrmex disciger, Acromyrmex ambiguus, and Acromyrmex hispidus. The last four were registered for the first time for the State of Goiás.